Periventricular nodular heterotopy of the gray matter: A case report - Youssef Hadzine, MD; Adel Elmekkaoui, MD; Othmane Benlenda, MD; Soukaina Wakrim, MD; Hicham Nassik, MD (Radiology Case Reports, 2022)
Periventricular focal nodular heterotopia is a rare secondary cerebral distortion caused by the interruption of neuronal migration from the periventricular germinal zone to the cortex during the fetal period. Clinically, it may manifest as epilepsy resistant to pharmacological treatments or rarely as mental retardation. We report a case of a six years-old male child who was subject to the intensive care unit for the management of refractory epilepsy. The diagnosis was done by magnetic resonance imaging of the brain, which revealed a nodular periventricular heterotopia of the gray matter. After the management of the status of epilepticus, the child remained spastic, aphasic with no contact with his environment.